Pengaruh Store Atmosfer, Persepsi Harga, dan Kualitas Pelayanan terhadap Keputusan Pembelian pada Cafe Wapress JK Pemalang - Dimas Maulana Priya Adtya Yudha; Tri Sulistyani; Makmur Sujarwo (Faculty of Economics and Business, University of Pancasakti Tegal, 2020)
Effect of Store atmosfer, Price persepsion and Service Quality on Decisions on Purchasing Cafe Wapress JK in Pemalang. Essay. Faculty of Economics and Business Pancasakti Tegal University.2019. Research Objectives: 1) to find out and analyze the influence of store atmosfer on the decision to buy Cafe Wapress JK Pemalang, 2) to find out the effect of price persepsion on the decision to purchase Cafe Wapress JK Pemalang, 3) to find out the effect of service quality on the decision to purchase Cafe Wapress JK Pemalang, 4) to find out store atmosfer, price persepsion and service qauality simultaneously on the decision to cafe Wapress JK Pemalang. Method of research is survey equal quantitave the population in this study ware consumer who purchased Cafe Wapress JK Pemalang. The sampling technique used was purposive sampling. The data analysis techenique used is Spearman rank correlation, speraman rank correlation significance test, multiple correlation analysis, test of significance of multiple correlation and coefficent of determination analysis. Research results: 1) there is a strong, positive and significant influence of store atmosfer has a significant effect on the decision to purchase in Cafe Wapress JK Pemalang. Barrier can be proven by obtaining value rxy is 0,747, significant value and Zcount value of 6,666 > 1,96, 2) there is a strong, positive and significant influence price persepsion has a significant effect on the decision to purchase in Cafe Wapress JK Pemalang. Barrier can be proven by obtaining value of rxy is 0,702, significant value and Zcount value of 7,731 > 1,96, 3) there is a strong, positive and significant influence service quality has a significant effect on the decision to purchase in cafe Wapress JK Pemalang.